Keterampilan Kolaborasi Mahasiswa PGSD dalam Mengembangkan Soal Literasi Matematis Melalui Kegiatan Lesson Study - Nur Safrida, Lela; Kristiana, Arika Indah; Alfarisi, Ridho (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to describe the collaborative skills of prospective elementary school teachers in developing mathematical literacy questions through lesson study activities. This type of research is quantitative descriptive research, namely describing collaboration skills based on data obtained through the stages of lesson study (plan, do, see). The research instrument used to answer the research objectives was a collaboration skills observation sheet. Based on the results of the data analysis, it can be concluded that students' overall collaboration skills have improved and are in the excellent category. A significant increase occurred in time management indicators due to students being able to complete assignments at the end of the final cycle. Keywords: collaboration skills, lesson study, mathematical literacy